2013
DOI: 10.1111/echo.12426
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Left Ventricular Contractility Abnormalities by Two‐Dimensional Speckle Tracking Strain in Chagas' Disease

Abstract: In a subgroup of asymptomatic patients with Chagas' disease without evident cardiac involvement, 2D strain was reduced compared with healthy individuals, suggesting incipient LV dysfunction in these patients. 2D ST strain has the potential for detecting early myocardial impairment in the setting of Chagas' disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 32 publications
6
55
1
6
Order By: Relevance
“…However, these measurements have major disadvantages, including angle dependence, limited spatial resolution, and deformation analysis in one dimension [9]. Two-dimensional (2D) speckle tracking echocardiography (STE) is a more effective method for objectively evaluating both the systolic and diastolic functions of the myocardium in detail [9][10][11]. STE assessment might be useful for identifying patients with subclinical LV dysfunction when the LV ejection fraction (LVEF) is normal on conventional echocardiography [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these measurements have major disadvantages, including angle dependence, limited spatial resolution, and deformation analysis in one dimension [9]. Two-dimensional (2D) speckle tracking echocardiography (STE) is a more effective method for objectively evaluating both the systolic and diastolic functions of the myocardium in detail [9][10][11]. STE assessment might be useful for identifying patients with subclinical LV dysfunction when the LV ejection fraction (LVEF) is normal on conventional echocardiography [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators, measuring ST globally, radially and circumferentially, showed a significant decreasing trend between the groups, with lower values of longitudinal strain in the CCM group compared with the control group (non‐ChD) in the midlateral, basal‐septal, basal‐anterior, and midanterior segments, and they found no differences in the longitudinal strain between the indeterminate patients and control group. Barbosa et al using a 2D longitudinal ST found a lower ST in the basal inferior, and inferoseptal walls, as well apical segment of the inferolateral wall compared to the control group . In contrast, we evidenced that GLS showed a significant decreasing trend across stages with an apparently sequential order in segmental wall impairment.…”
Section: Discussionmentioning
confidence: 92%
“…However, as this assessment relies on visual judgment, assessments of endocardial excursion are subjective and have a high interobserver variability. 25,[27][28][29][30] A recent study by Simsek et al 18 involving elite young athletes compared marathon runners and wrestlers. However, TDI is characterized with limitations in angle dependence, limited spatial resolution, and deformation analysis in 1 dimension.…”
Section: Discussionmentioning
confidence: 99%
“…This new technique enables a better evaluation of myocardial contraction and relaxation. 25,[27][28][29][30] A recent study by Simsek et al 18 involving elite young athletes compared marathon runners and wrestlers. While the systolic and diastolic functions evaluated by conventional echocardiography were similar, LV GLS strain and strain rate values were greater in both marathon runners and wrestlers than in the control group.…”
Section: Discussionmentioning
confidence: 99%